Combinatorial library strategies for synthesis of cationic lipid-like nanoparticles and their potential medical applications. (March 2015) - Altınoglu, Sarah; Wang, Ming; Xu, Qiaobing
The past two decades have witnessed the high efficiency and efficacy of cationic lipids and liposomal formations for drug delivery. The tedious synthesis of conventional lipids and the inefficiency in studying structure–activity relationships, however, have hindered the clinical translation of lipid nanoparticle delivery systems. Combinatorial synthesis of lipid-like nanoparticles ('lipidoids') has recently emerged as an approach to accelerate the development of these delivery platforms. Utilizing a high-throughput screening strategy, the libraries of lipidoids are sorted and prime candidates for the delivery in the intended application can be identified and optimized for the next generation. In this review, we outline methods used for combinatorial lipidoid synthesis, the application of high-throughput screening, and the current medical applications of candidate lipidoids.